The Norwegian‐Greenland Sea, the Laschamps, and the Mono Lake Excursions Recorded in a Black Sea Sedimentary Sequence Spanning From 68.9 to 14.5 ka. Issue 8 (24th August 2020) - Liu, Jiabo; Nowaczyk, Norbert R.; Panovska, Sanja; Korte, Monika; Arz, Helge W.
Abstract: A full‐vector paleomagnetic record, comprising directional data and relative paleointensity (rPI), was derived from 16 sediment cores recovered from the southeastern Black Sea. The obtained data were used to create a stack covering the time window between 68.9 and 14.5 ka. Age models are based on radiocarbon dating and correlations of warming/cooling cycles monitored by high‐resolution X‐ray fluorescence (XRF) elementary ratios and by ice‐rafted debris (IRD) in Black Sea sediments to the sequence of "Dansgaard‐Oeschger" (D‐O) events defined from the Greenland ice core oxygen isotope stratigraphy. The reconstructed prominent lows in paleointensity at about 64.5, 41.2, and 34.5 ka are coeval with the Norwegian‐Greenland Sea, the Laschamps, and the Mono Lake excursions, respectively. For a further analysis, the stacked Black Sea paleomagnetic record was converted into one component being parallel to the direction expected from a geocentric axial dipole (GAD) and two components perpendicular to it (EW, inclined NS), representing definitely only non‐GAD components of the geomagnetic field. Discussions of the field configurations at the Black Sea site are focused on the three excursional events. The Norwegian‐Greenland Sea excursion was dominated by a decaying axial dipole and persisting weak nondipole field, with directional variations still within the range of normal secular variations. The Laschamps excursion comprises two full polarity transitions and a short stable interval of reversed polarity in between. The Mono Lake excursion was mostly dominated by a nondipole field, though with a less pronounced weakening of the axial dipole component. Key Points: Reconstructed paleosecular variation record between 68.9 and 14.5 ka from Black Sea sediments Increasing axial dipole component with reversed polarity during the midpoint of the Laschamps excursion Comparable levels of dipole and nondipole contributions during the Mono Lake excursion